The current state and prospects of China’s environmental, social, and governance policies - Ju, Binbin; Shi, Xiaonan; Mei, Yueru (Frontiers in Environmental Science, 2022)
In recent years, the problem of global climate change has become increasingly prominent, which brings great inconvenience to people’s production and life. China is a major participant in global climate governance. Especially, enterprises are one of the important participants in climate change governance. And the development of ESG concept is highly unified with the realization of global climate change Governance and the goal of “Double Carbon”. But the development of ESG in China still faces many challenges. Based on this, this paper mainly combs the current situation and existing problems of ESG development in China. We put forward ESG suitable for the development of China's national conditions and policy suggestions. Finally, in the context of environmental protection and resource conservation, help enterprises achieve sustainable development.